The platelet P2 receptors in inflammation - Cattaneo, M. (Hämostaseologie, 2015)
In addition to their well characterized and established role in haemostasis and thrombosis, platelets contribute to the pathogenesis of inflammation. Adenine nucleotides are signalling molecules that regulate the function of virtually every cell in the body, by interacting with P2 receptors. Their important role in inflammation is well established. In the last few years, the pro-inflammatory roles of adenine nucleotides interacting with their platelet P2 receptors has emerged. In particular, it was shown that the platelet P2Y12 receptor for ADP significantly contributed to the proinflammatory effects of cysteinyl leukotrienes (CysLT) in experimental models of asthma in mice. More importantly, it was recently shown that P2Y12 variants were associated with lung function in a large family-based asthma cohort and that the P2Y12 antagonist prasugrel tended to decrease bronchial hyper-reactivity to mannitol in patients with allergic bronchial asthma in a randomized, placebo controlled trial.These data strongly suggest that P2Y12 may represent an important pharmacological target for the treatment of patients with allergic bronchial asthma.
Keywords: P2Y12; asthma; inflammation; platelets; cysteinyl leukotriens